Comprehensive Analysis of Latex Additives for Zonal Isolation and Gas Migration Control - Pattinasarany, Adrian; Lian, Dan (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This paper examines the performance of a latex additive in a 7-inch production casing cementing operation, focusing on its role in improving zonal isolation and preventing gas migration. The study uses data from, Cement Hydration Analyzer (CHA), Static Gel Strength Analyzer (SGSA), Cement Bond Logs (CBL), and Ultrasonic Imaging Tools (USIT) to assess the latex additive's impact on cement bond quality and integrity. Primary cementing practices are critical for ensuring well integrity and productivity. Latex additives strengthen the bond between casing and formations, improving zonal isolation and gas migration control. These additives enhance the mechanical properties of cement slurries, creating a resilient seal for hydrocarbon production demands. Advanced technologies like CHA and SGSA provide real-time monitoring of the cement hydration process, offering valuable views into mechanical property development and potential weaknesses in preventing fluid migration. The study shows how latex additives optimize hydrocarbon extraction, safeguard well integrity, and develop new methods to mitigate gas migration. It is concluded that using latex additives, combined with simulations to analyze displacement efficiency, flow potential, and critical static gel strength, enhances cementing operations and prevents gas migration. This approach may also lead to cost savings by potentially eliminating the need for ultrasonic logging in future latex jobs.